Calculus : concepts and contexts - Stewart, James (Australia : Thomson Learning Asia, 2001)
The principal way in which this book differs from more traditional textbooks is that it is more streamlined. For instance, there is no complete chapter on techniques of integration. The data in examples and exercises have been updated to be more timely.
A preview of calculus -- Chapter1. Functions and models -- Chapter2. Limits and derivatives -- Chapter3. Differentiation rules -- Chapter4. Applications of differentiation -- Chapter5. Integrals -- Chapter6. Applications of integration -- Chapter7. Differential equations -- Chapter8. Infinite sequences and series -- Chapter9. Vectors and the geometry of space -- Chapter10. Vector functions -- Chapter11. Partial derivatives -- Chapter12. Multiple integrals -- Chapter13. Vector calculus.
Includes index.
Keywords: CALCULUS